Aggersund-bopladsen zoologisk belyst. Svanejagt som årsag til bosættelse? - Møhl, Ulrik (Jysk Arkæologisk Selskab, 1978)
Zoological analysis of the Aggersund settlement: a special-purpose camp for hunting swans? The settlement at Aggersund is one of the many coastal sites in Jutland containing material belonging to the Ertebølle culture. It has been dated by means of carbon-14 to 3400 BC. It is situated on the north coast of the Limfjord, about 1 km N. N. E. of Aggersund. The tools and animal bones from the site show it to be a pure hunting camp, exploiting both terrestrial and marine resources. When this settlement, despite its 'usual' content of artifacts, bones and shells, is examined from the zoological point of view, it is done not in order to increase knowledge of the local fauna, etc., which is already well known from earlier excavations yielding much more material; on the contrary, the value of this settlement ties in its small size, representing a brief period of settlement. Besides this it has been completely excavated, and its limited contents of bones and shells are suited to an analysis of the absolute number of animals, season of occupation, length of occupation, and the number of people present. Such calculations are often problematic, but can to some extent be used to support each other. The bone material (table I) included a number of fragments from which could be calculated the age of the animal, on the basis of the eruption and wear of teeth (fig. 2:1-4 and 3:2), and also a number of seasonal species such as the Whooper Swan (Cygnus cygnus) which is assumed to have migrated in a similar manner to the present day. Identifiable bones are briefly listed by species, and the minimum individual counts given are based on the bones and teeth shown in fig. 1-4. Taken together all the evidence points to a winter occupation. The four young wild pigs are about 6, 8, 10 and 18 months old (period of birth: March-May), white the young red deer is judged to be about 1½ years of age, the wear of its rearmost tooth (deciduous P4) corresponding to a recent animal from Jutland killed in December. The Whooper Swans (fig. 4), present in large numbers (see below) are winter visitors, being present in Denmark between November and April. Besides these definite winter indicators, mention can be made of the fur-bearing marten and fox (fig. 1:1 and 2), the skins of which are at their best during the first half of the winter; the hunters of that time would have had detailed knowledge of skins and their quality. Evidence contrary to the theory of winter occupation is completely lacking; no bones or ageable teeth were found which could be taken as evidence of spring or summer occupation. Some of the animals, e.g. the two adult wild pigs (one sow and one boar) and the grey seal, can give no evidence of the season of death, and could have been killed outside the suggested period of settlement; however, in view of the above evidence this seems unlikely. The subtitle, 'a special-purpose camp for hunting swans' puts forward the suggestion that these birds might have been the principal reason for the existence of the small settlement. It is well known that bones of Whooper swan (Cygnus cygnus) and Bewick's swan (C. bewickii) often occur in the Ertebølle culture's coastal sites, and one may assume that these swans were, in the winter, very common around the Limfjord and other shallow bays, fjords and inlets, and that the hunters of the period well knew at what time of year they appeared. No bones of the Mute swan (C. olor) are known from settlement of the Ertebølle period. In this analysis less importance is attached to the value of the meat of these birds than to the skin, which is regarded as the most important reason for the hunting of these birds. This is supported by more recent evidence, in that the cured skins of seabirds (divers, eider etc.) are still, though in ever smaller numbers, used on Greenland; also older written records indicate the use of cured swan skins in Sweden (Bernstrom 1972), including the fact that in 1548 the wardrobe of King Gustav I included 2 swanskins as well as the unused skins of the breasts of three swans. From Denmark there is the information that in 1786 a tanner applied for permission to kill swans on the shore near Copenhagen; only the skins of old birds were used (Weismann 1931). Together these various glimpses of the use of cured swan and seabird skins give the impression of their considerable importance still further back in time. Mention in traditions and legends of people 'clad in swanskin' is evidence of this, and of a widespread awareness of the usefulness of swan skin. Despite long periods with no information, it is possible by means of fortunate finds to give evidence of the value of swans -even over and above just their utility value- as far back as the hunting period of the stone age, to which the settlement of Aggersund belongs. In the bog of Aamosen in central Zealand was found in 1940 a skeleton of a woman dated to the subboreal period, which was buried together with a swan, and during the excavation in 1975 at Vedbaek, north of Copenhagen, of a cemetery from the Atlantic period, a grave was excavated containing the skeleton of a woman, by the right side of which lay the skeleton of a newborn child -laid to rest on a swan's wing. One suspects that these finds have a connection with transportation to the otherworld. Thus there are archaeological grounds for supposing that stone age swan hunting was important in a variety of ways, ranging from the use of the meat, through clothing, to the religious. It is not possible to state the manner by which swan hunters pursued their prey, although one find -also from Vedbaek- does give a suggestion, inasmuch as a find was made in 1973 of a swan proximal humerus in which was lodged a transverse arrowhead. This is in accord with present views of stone age hunting, but it must be added that much game was presumably procured by other methods which have not left any evidence -such as snares, traps, nets and pitfalls, etc. As with other Ertebølle-period settlements, Aggersund is characterized by the presence of numerous oystershells, among which other species, as usual, also occur in smaller numbers (table I and p. 10). At Aggersund over 90% of all shells are oysters. Samples analysed quantitatively lead to the conclusion that the total number of oysters present is in the region of 6000. These oysters, as far as food value is concerned (calculated in terms of calorific content), have only a subsidiary importance, but these shells are nonetheless typically present in large numbers on settlements from a long period of the stone age. It is therefore suggested that the chemical content of these shells, in particular iron compounds, zinc, iodine, and salts, rather than just their food value, was the indirect reason for the accumulation of the large shell middens. This hypothesis neither ignores nor rules out other values of shellfish from the purely culinary, to their use as an addition to the drier meat of mammals and birds, and as a means of survival in critical periods. In calculating the quantity of meat the 'minimum individuals' count is used; for various reasons it appears that this is not far removed from the actual number of animals present. The total number of animals is calculated to have weighed about 1000 kg as killed, yielding some 600 kg of edible meat. The fur bearing animals have not been included in the calculations, because evidence from this and other sites implies that these animals were not normally eaten; oysters are also left out of the meat weight calculations, but are included in table II as a not unimportant addition. In table II are included some of the possible combinations of number of people present and total length of stay, based on the quantity of meat and oysters, all with reference to fig. 5, which shows the yearly cycle and the most likely period of occupation (shaded) within which all seasonal indicators could coincide. No evidence falls outside this period. The material can however give no certainty that occupation was continuous within the probable period of occupation. Mention must also be made of the many possible sources of error involved in such uncertain calculations, which by their very nature produce uncheckable figures which are then used as the basis for further calculations. The above is therefore to be regarded as an idealised, and as far as possible accurate, attempt to interpret the few pieces of information available in the material from a small, completely excavated shell-mounds. Ulrik Møhl